Vestibular schwannoma: a therapeutic challenge - Ponce, Gabriel; Velásquez, Anghelo; Flores, Jerson; Mejia, Marco; Vargas-Urbina, John (Revista Argentina de Neurocirugía, 2025)
Background: vestibular schwannoma (VS) is a benign brain pathology, and its incidence increases with age. It is the most common benign tumor of the posterior fossa. Objectives: to report the pre- and post-surgical results of patients undergoing vestibular schwannoma resection and to compare the post-surgical data with the published literature. Methods: the medical records of patients with VS who underwent surgery at our institution in the last two years were reviewed. A retro sigmoid craniotomy was performed in all cases. The House-Brackmann scale was used to assess facial nerve function and the AAO-HNS (American Academy of Otolaryngology–Head and Neck Surgery) scale for the vestibular nerve. Statistical analysis was completed using SPSS software. Results: twenty-one patients, with an average age of 52.3 years. 52.4% were Koss IV. Grade D hearing loss was present in 47.7%. Headaches were presented in 47.6%, facial hypoesthesia in 95.2% and grade II facial paresis in 38%. Resection was total in 95.3%. Facial nerve injury occurred in 19%. CSF fistula in 14.2%. 66% of patients evolved favorably, presenting HB I and II paresis. Our percentage of Koss IV tumors was 52%. Regarding the degree of resection, we obtained a resection greater than 95%. Conclusion: The evolution was favorable and the postoperative results acceptable.